(3TQM ThGgO CHjGJ TQM GdNdGUIs - (3eMeO Hf Ydj GdehShjs ((3MSf Hf eMeO Ydj Hf MJQhTs)
(3ChdgG (B:s
.. (3YHf GdaYd ceG aj QLd TGFc hMGUd GdeYfi Gfc JbUO SfGhGJce CQV eQJaY ZGQgG Hjfc hHjfg jUa HYO GdWQjb hCf Hjfg hHjf SfGf ef GdCQV eG GdeWeFf efg eMOhO (B...s
(3BNQgG (B:s
.. (3bOe aj ThGgO fhfj GdJhcjO eaSQG HeG dG eRjO Ydjg hGdTGgO aj GKHGJ GdgeRI ef jDcO eG ddVQhQI hgPG BNQ eG YeOJ Edi TQMg ef ThGgO CHjGJ TQM GdNdGUI (B.s
(3JHUQI GdYfhGf (B:s
(3TQM ThGgO CHjGJ TQM GdNdGUIs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GddZIs